2014
DOI: 10.1016/j.jagp.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Concerns and Neuropsychiatric Predictors of Progression to the Early Clinical Stages of Alzheimer Disease

Abstract: Objectives To examine neuropsychiatric and neuropsychological predictors of progression from normal to early clinical stages of Alzheimer’s disease (AD). Design Longitudinal study Setting Massachusetts Alzheimer’s Disease Research Center longitudinal cohort Participants From a total sample of 559 older adults, 454 were included in the primary analysis: 283 with clinically normal cognition (CN), 115 with mild cognitive impairment (MCI) and 56 with subjective cognitive concerns (SCC) but no objective impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(154 citation statements)
references
References 43 publications
6
146
0
2
Order By: Relevance
“…A recent study compared baseline characteristics of progressing and non-progressing SMI subjects and reported that progressing subjects were older and had more AD biomarkers in the cerebrospinal fluid [6] . Another study reported that SMI subjects with APOE4 had a higher amyloid deposition, suggesting preclinical AD [16] . A cohort study composed of normal elderly and patients with subjective cognitive impairment and MCI reported that low scores in memory, naming, and semantic fluency predicted rapid progression across all groups [17] .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study compared baseline characteristics of progressing and non-progressing SMI subjects and reported that progressing subjects were older and had more AD biomarkers in the cerebrospinal fluid [6] . Another study reported that SMI subjects with APOE4 had a higher amyloid deposition, suggesting preclinical AD [16] . A cohort study composed of normal elderly and patients with subjective cognitive impairment and MCI reported that low scores in memory, naming, and semantic fluency predicted rapid progression across all groups [17] .…”
Section: Discussionmentioning
confidence: 98%
“…Subjective cognitive complaints, loss, or impairment were defined in 5 studies 17,21,22,24,25 by a positive answer to any of 2 questions: ''do you feel like your memory is becoming worse'' or ''do you have problems with your memory.'' One study used both informant-based and selfbased reports to define SMC, 18 and another identified 4 groups based on investigator judgment during an interview: no complaints, self-complaints, and informant complaints in the absence or in the presence of self-complaints. 19 A positive score on the Multidimensional Assessment of Neurodegenerative Symptoms was used as a definition of cognitive complaint by the last one.…”
Section: General Characteristicsmentioning
confidence: 99%
“…[13] While chronic late life major depression (LLD) confers the greatest risk of transition to MCI[3], other forms of depression, such as intermittent and remitted major depression[3], or low-grade depressive symptoms measured by depression screening instruments[4] or as a neuropsychiatric symptom item[1, 3] are also associated with increased risk of cognitive decline in older individuals without objective cognitive impairment. Here, the term “subthreshold symptoms of depression” (SSD) is used to encompass lower severity depressive classifications that do not meet diagnostic criteria for major depression, such as subsyndromal depression and minor depression, as well as depressive symptoms within a low or subclinical range on depression scales.…”
Section: Introductionmentioning
confidence: 99%